Restorative Justice: Antithesis or New Face of The Punishment Model? - Susilo, Erwin; Sujatmiko, Bagus; Mawla Ibnu Kamali , Karell (Legitimasi: Jurnal Hukum Pidana dan Politik Hukum, 2025)
Restorative Justice is increasingly adopted to overcome the limitations of retributive punishment, which emphasizes inflicting suffering on offenders. However, a fundamental theoretical debate remains regarding the ontological status of Restorative Justice: whether it is merely a non-penal mechanism outside the concept of punishment or a transformative form of punishment within the modern penal framework. This research examines this debate by determining the proper positioning of Restorative Justice in modern sentencing policy. The purpose of this study is to reconstruct the penal paradigm by integrating restorative, utilitarian, and moral-communitarian values into a more humane and inclusive system of punishment. Using normative legal research with a conceptual approach, this study analyzes theories, legislation, and judicial practices related to Restorative Justice in Indonesia. The findings suggest that Restorative Justice still retains punitive elements, as offenders are required to acknowledge wrongdoing and repair the harm. Consequently, Restorative Justice ought not to be classified as an exclusively non-penal mechanism but rather as an evolution of punishment that prioritizes reconciliation, moral accountability, and social restoration. This study concludes that Restorative Justice represents the new face of punishment, where the ultimate aim is no longer solely retribution but the restoration of social balance and substantive justice for victims, offenders, and society.